THE INFLUENCE OF THE RECRUITMENT AND SELECTION PROCESS ON EMPLOYEE PERFORMANCE AT DEANDRA BATIK TULIS LAMPUNG - Anissa Putri Sarasati; Defrizal Defrizal (ZILLZELL MEDIA PRIMA, 2024)
The purpose of this study was to determine the extent of the recruitment and selection process for employee performance at Deandra Batik Tulis Lampung. This study used a quantitative approach using questionnaire or questionnaire methods. This study used primary data. Primary data is data generated from questionnaires that have been filled out completely and distributed to all employees, in this case Deandra Batik Tulis Lampung company owner in Lampung and employees totaling 39 people ranging from pattern making, polishing and repair. Recruitment and selection research on hypothesis testing partially shows the presence of significant influence on the performance of Deandra Batik Tulis Lampung employees. Furthermore, together the variables of selection and recruitment of employees affect employee performance together.